First analysis of in situ observation of surface Alfvén Waves in an ICME flux rope - Raghav, Anil; Dhamane, Omkar; Shaikh, Zubair; Azmi, Naba; Manjrekar, Ankita; Panchal, Utsav; Ghag, Kalpesh; Telloni, Daniele; D’Amicis, Raffaella; Tari, Prathmesh; Gurav, Akshata (My University, 2023)
Alfvén waves (AWs) are ubiquitous in space and astrophysical plasma. Their crucial role in various physical processes has triggered intense research in solar–terrestrial physics. Simulation studies have proposed the generation of AWs along the surface of a cylindrical flux rope, referred to as surface AWs (SAWs); however, the observational verification of this distinct wave has been elusive to date. We report the first in situ observation of SAWs in a flux rope of an interplanetary coronal mass ejection. We apply the Walén test to identify them. We have used Elsässer variables to estimate the characteristics of SAWs. They may be excited by the movement of the flux rope’s footpoints or by instabilities along the boundaries of the plasma magnetic cloud. Here, the change in plasma density or field strength in the surface-aligned magnetic field may trigger SAWs.
Keywords: Alfven waves; Space plasmas; Solar coronal mass ejections